Achillea millefolium Linn. A Comprehensive Review of its Unani Description, Therapeutic Potential and Phytochemical Diver - Suheena Khanday; Ghazala Javed; Mohd. Afsahul Kalam; Aamir Yousuf; Iqra Rifat (International Journal of Phytomedicine, 2025)
Commonly referred to as yarrow, Achillea millefolium Linn. is an upright perennial plant in the Asteraceae family. It is widely found in temperate regions and has long been used for its therapeutic qualities, especially in Chinese, Native American, European, and Greek traditional medicine. The pharmacological properties of yarrow are well known and include anti-inflammatory, antibacterial, antioxidant, lithotriptic, carminative, and hemostatic actions. The plant's aerial parts are very useful for treating phlegm-related conditions, stimulating the generation of bile, and functioning as a diuretic and bitter digestive tonic. Its abundance of bioactive substances, including flavonoids, terpenes, alkaloids, and essential oils, is largely responsible for these qualities. In order to lay the groundwork for future study directions, this paper attempts to thoroughly examine the morphology, phytochemistry, and pharmacological characteristics of yarrow.